Do Functionally Fit Elderly Community-Dwelling Subjects Have Enough Time to Safely Cross the Road? - Rugelj, Darija; Tomšič, Marija; Sevšek, France (Promet - Traffic&Transportation, 2013)
Elderly people are the most vulnerable group in urban traffic and a large proportion of them are as pedestrians victims of traffic accidents. The majority of these happen while crossing the road. Crossing a busy road at an intersection with traffic lights or without them is a typical dual task condition requiring a motor task i.e. walking and a cognitive task such as monitoring traffic. The purpose of present study was to compare the walking speed and the related spatio-temporal gait variables of fallers and non-fallers in three walking conditions against the speeds required by regulations in Slovenia for safe street crossing. To assess the spatio-temporal characteristics of gait we used a 7m instrumented walkway. The general results showed that the spatio-temporal gait parameters did not differ between the two groups at the self-selected speed. But as soon as a constraint, such as fast walking speed, was imposed on the subjects the differences between the groups became evident. Fallers demonstrated a significantly slower mean gait velocity and shorter stride length while the cadence and the base of support did not differ between the two groups. In dual task conditions the difference between the two groups reached 25 percent. The fallers group gait velocity dropped to 0.99 m/s. The observed walking speed was slower than considered by the guidelines for the design of traffic light equipped road crossing. In conclusion, the results of walking speed under dual task conditions could be a useful parameter for planning of optimal pedestrian crossing in urban areas. These results will serve for the design of a population based study in Ljubljana.